Comparative Colonisation Ability of Human Faecal Microbiome Transplantation Strategies in Murine Models - Bon‐Hee Gu; Ho Young Jung; Chae‐Yun Rim; Tae‐Yong Kim; Sang‐Jin Lee; Doo Young Choi; Han‐Ki Park; Myunghoo Kim (Microbial Biotechnology)
ABSTRACT The gut microbiome plays a crucial role in maintaining intestinal homeostasis and influencing immune‐mediated diseases. Human faecal microbiota transplantation (FMT) is often employed in murine models to investigate the role of human microbes in disease regulation, but methods for effective colonisation require refinement. This study aimed to assess the colonisation efficiency of human microbiota in a murine model using FMT with human faeces, focusing particularly on the impact of gut microbiota depletion via polyethylene glycol (PEG) and comparing oral‐gastric gavage with enema administration routes. Our findings revealed that PEG‐induced depletion enhanced human microbiome colonisation in mice. Oral‐gastric gavage prolonged colonisation, while enema administration facilitated quicker resolution of dysbiosis, both inducing selective human microbial colonisation in a time‐dependent manner. Notably, genera such as Bacteroides, Blautia, Medicaternibacter and Bifidobacteria were successfully colonised, whereas Roseburia, Anaerostipes, Anaerobutyricum and Faecalibacterium failed to establish in the murine gut post‐FMT. These findings highlight the challenges of replicating human gut microbiota in murine models and underscore the importance of selecting appropriate FMT methods based on desired outcomes. This study provides valuable insights into the colonisation dynamics of human microbiota in mice, contributing to the development of more effective FMT strategies for disease treatment.